Analisis Penggunaan Alat Peraga Mobil Tenaga Surya sebagai Media Pebelajaran terhadap Minat Belajar Siswa pada Materi Energi Alternatif - Nicolaus Hilary Kokan Uran; Yustina Yesisanita Yeyen; Bertolomeus Haryanto Agung (Departement of Mathematics Education, 2024)
Teaching aids in learning are tools used by teachers to explain material or transfer knowledge to students. This research aims to analyze the effect of using solar powered car props on students learning interest in alternative energy material. This research was conducted at St John Paul II Catholic High School, Maumere. This type of research is descriptive qualitative. The research subjects are students of class X-1 Tahm Pelajgran 2023/2024 with a total of 30 students. The data collection technique was carried out by distributing questionnaires, or questionnaires. The instruments used were student response questionnaires to teaching aids and student interest questionnaires. Before distributing the questionnaire, validation is carried out first on the questionnaire. Validation of the student response questionnaire to teaching aids and validation of the learning interest questionnaire obtained a percentage score of 85% and 95% so that it was declared valid and suitable for use. Data anlysis was carried out by calculating the average percentage of each indicator and then describing it qualitatively and obtained a total percentage of interest in learning which was 87,25% and the total percentage of student responses to teaching aids was 87,3% and it can be seen the relationship between student interest in learning and student responses to teaching aids.